Investigating the association between the lunar cycle and sleep, physiological, cognitive, and physical performance in children with Down syndrome - Zohra Lammouchi; Noomen Guelmami; Salma Abedelmalek; Mouna Saidane; Hatem Ghouili; Mahmoud Rebhi; Mohamed Saifedine Fessi; Mohamed Ben Aissa; Hafsi Bedhioufi; Helmi Ben Saad; Ismail Dergaa (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Children with Down syndrome (DS) offer a compelling context within the fieldof human biology for examining potential lunar influences. While the exact mechanisms governing lunar effects are still under investigation, a growing body of scientific inquiry suggests possible connections between lunar phases and physiological, physical, and cognitive parameters. This investigation holds promise for uncovering the intricate interplay between lunar cycles (LCs) and the unique biology of children with DS. This study investigated the potential influence of the LC on physiological, physical, and cognitive parameters in children with DS, focusing on sleep patterns, physical performance, and cognitive abilities. MATERIALS AND METHODS: Seventeen children with DS participated in this study. Sleep data, physical performance metrics, and cognitive test results were collected throughout the LC, including the new moon (NM), first quarter, full moon (FM), and third quarter. Statistical analyses were conducted to assess the differences in these parameters across lunar phases. RESULTS: Significant differences were observed in sleep patterns, with reduced total sleep time (P < 0.01) and sleep efficiency (P < 0.001) during the FM phase. Heart rates (HRs) before (P < 0.001) and after (P < 0.01) exercise also displayed pronounced changes during LC. Additionally, the reaction time (RT) exhibited a significant difference (P < 0.01) across the lunar phases. However, physical performance metrics, including squat jump (SJ), sprint, and 6-minute walk distance (6MWD), did not show significant variations. CONCLUSION: This study suggests that LC may have a moderating effect on sleep patterns, HR, and cognitive performance in children with DS. These findings have practical implications for caregivers and educators and highlight the importance of considering lunar-associated variations in planning schedules and interventions for children with DS.